Calgary Family Intervention Model Approach ( CFIM ) Prevention of Food Borne Disease and Self Care Agency for Children - Wiwit Dwi Nurbadriyah (University of Muhammadiyah Malang, 2016)
Food borne disease (FBD) is a disease caused by consumption of contaminated food. The problem is, school aged children are vulnerable Food borne disease because of household food contamination. This indicates the family hygiene as a food handler mainly mother during preparing the food still need to be improved. The study design used pre experiment one group pre and post test design with a sample of 35 respondents namely, 4th grade students with their parents and 5th grade students with their parentsin Jatirejoyoso Kepanjen Primary School. Demographic data, CFAM (Calgary Family Assessment Model), knowledge, attitudes, practices family and children's self-care agency in PHBS at school were used.The results was an increase in knowledge and attitudes of families, family practice and self child care agency did not change after the intervention CFIM for 4 sessions. CFAM on the functional components of the daily activity was lacking mostly, thus affecting the unchanged practice. While children self-care agency was affected by school environment such as affordability of snacks. Health professionals are expected to optimize School Health Unit program to provide education about clean and healthy living behaviors at the school community (students, teachers and school employees) and family assistance through a cadre.